Formação em enfermagem orientada pela integralidade : indicadores presentes em projetos pedagógicos de cursos de graduação do Rio Grande do Sul - Estima, Sonara Lúcia (2010)
Higher education institutions have mobilized knowledge and practices in order to develop the learning of integrality, fundamental principle of SUS, and a constant item in the guidelines for training in all health professions. This study aimed to verify the presence of integrality indicators in Pedagogical Projects in Nursing Undergraduate Courses in Rio Grande do Sul, from the imposition of DCN (National Curricular Guidelines); map integrality indicators according to the categories established in the study; analyze the integrality of indicators and verify their use as theoretical and epistemological foundation for the formation of these health professionals. Given the qualitative nature of the study, a methodology of documental research was used. The documents analyzed for the formation of the corpus were the pedagogical projects of Nursing Graduate Programs in Rio Grande do Sul. The categories analysis composition referenced the Analytical Matrix of the experiences of integrality teaching, from the project Ensina SUS: Practices and processes in training and care, adapted to the objectives of the study. The categories were: Institutional pedagogical-political processes/relationships in health, Content Selection, Learning Scenarios and Care Networks. Considering these categories we infer that the training of nurses is a field in which the entire premise is for the reorganization of health practices, since it determines the acquisition of competencies and skills for professional practice. That requires an understanding of education as a process built by different actors that move as subjects that determine health, education and social control practices, including intersubjective situations and a set of ethical and moral values. We conclude that the learning of integrality in health care is shown in the production of a care that is effective, humanized and effectively focused on the needs of individual and collective users of health services. It is expected that schools prepare highly qualified health professionals with skills and abilities to provide health care in line with the principles of SUS, guided by the logic of integrality and humanization of care.